OPTIMALISASI MODEL PEMENUHAN ZAKAT PERTANIAN BERBASIS MUZARA’AH YANG BERKELANJUTAN - Nurlela Kadir Nurlela Kadir (Department of Management Zakat and Waqf, 2025)
The purpose of this study is the fulfillment of agricultural zakat is fulfilled in the Muzara’ah system in agricultural land, this study contributes to farmers and landowners and the community to maximize the potential of agricultural products so that zakat obligations can be fulfilled more effectively and fairly by the parties involved in agricultural cooperation. This study uses a qualitative approach and collects data using field research methods, with data collection techniques through interviews. The results of the study indicate that the sustainable Muzara’ah based agricultural zakat fulfillment model in Duampanua District, Pinrang Regency requires efforts to increase farmers’ understanding of zakat obligations in accordance with the agricultural products they manage. Although there are two profit sharing systems applied, zakat awareness among farmers is still limited, especially related to agricultural zakat in the context of Muzara’ah. Further counseling is needed to improve the understanding of farmers and landowners. Although the Muzara’ah system is generally in accordance with Islamic economic principles, challenges arise due to doubts regarding oral agreements. Therefore, strengthening the role of BAZNAS and UPZ at the sub district level, as well as utilizing cooperation with Islamic missionary institutions is very important so that zakat ibligations can be implemented optimally and sustainably.